The The Contemporary State of Transportation in India after COVID-19 Spread- The Travelers’ Perspective - Singh, KULDEEP (Turizam, 2022)
In the process of unlocking India after the COVID-19 outbreak, the travel and tourism industry is resuming to revive the economy. It is substantial to examine the contemporary state of transportation in India and travelers’ perspectives post COVID-19 spread. The descriptive study is aimed to investigate the effect of COVID-19 on travel patterns of Indians, their tour plans, readiness for availing transportation services, and perspectives regarding the reoperation of transportation services in India. For this study, an online survey was conducted to gather primary data. A total of 212 responses were collected through convenient sampling. This study revealed that COVID-19 has extremely affected the perspectives and choices of people regarding different transportation services. They consider transportation a major cause of spreading the Coronavirus and the railway was considered the riskiest. Although half of the respondents reported their readiness to avail public transportation and stated that reoperation of transportation services was done on time. However private vehicles were their priority not only for their regular travels but for future tours also. Travelers were doubtful about the effective implementation of rules and regulations in public transportation in India. The study provides useful understandings to the tourism & transportation authorities and operators regarding the travelers’ perspective concerning transportation amid COVID-19. For further research, the perspective of transportation operators can be investigated for valuable insights and longitudinal research can also provide in-depth understandings.